Trilobite compound eyes with crystalline cones and rhabdoms show mandibulate affinities - Gerhard Scholtz (Nature Portfolio, 2019)
Little is known about the internal anatomy of early eyes. Here, Scholtz and colleagues show the internal eye structures from fossils of two genera of trilobites, which support an ancestral apposition eye with crystalline cones in Trilobita and a close affinity with Mandibulata.